Down-Regulation of PDCD4 Promotes Proliferation, Angiogenesis and Tumorigenesis in Glioma Cells - Pin, Guo; Huanting, Li; Chengzhan, Zhu; Xinjuan, Kong; Yugong, Feng; Wei, Liu; Shifang, Li; Zhaojian, Li; Kun, Han; Weicheng, Yao; Yingying, Lin; Yongming, Qiu; et al. (Frontiers in Cell and Developmental Biology, 2020)
The programmed cell death 4 (PDCD4) tumor-suppressor gene regulates cell apoptosis, protein translation, signal transduction, and induction of mediators of inflammation. However, the mechanism by which PDCD4 is down-regulated and regulates tumor growth remains elusive. In this study, we showed that PDCD4 is down-regulated in glioma cells and acts as a tumor suppressor. Based on the TCGA data, we confirmed that AKT2, but not AKT1 or AKT3, interacts with PDCD4, thus leading to the suppression of PDCD4 in glioma cells. Moreover, the analysis suggested that PDCD4 regulates the expression of IL-5, CCL-5, VEGF, and CXCL10 via the NF-kB pathway. Additionally, depletion of levels of PDCD4 promoted angiogenic activity of glioma cells via the VEGF-STAT3 pathway. When tumor cells over-expressing PDCD4 were injected into nude mice, the increased expression of PDCD4 blocked tumorigenesis and prolonged overall survival. Our study indicates the need to develop drugs that can modulate the expression of PDCD4 and test their efficacy in clinical trials.